2023
DOI: 10.1021/acsomega.3c03592
|View full text |Cite
|
Sign up to set email alerts
|

Anticorrosion Investigation of New Diazene-Based Schiff Base Derivatives as Safe Corrosion Inhibitors for API X65 Steel Pipelines in Acidic Oilfield Formation Water: Synthesis, Experimental, and Computational Studies

Amal A Altalhi

Abstract: The current study examines the evaluation of diazene-based Schiff base derivatives, namely, 4-((E)-(3-((E)-(hexylimino)methyl)-4-hydroxyphenyl)diazenyl)benzonitrile (S1) and 4-((E)-(3-((E)-(dodecylimino) methyl)-4-hydroxyphenyl)diazenyl)benzonitrile (S2). The structure elucidation of prepared the Schiff base compounds was performed by FTIR, 1 H NMR, and 13C NMR. In addition, the corrosion inhibition capacity of these compounds was investigated for API X65 steel pipelines in 1 M HCl utilizing gravimetric and el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…32 The relevant electrochemical parameters including corrosion potential ( E corr ), corrosion current density ( i corr ), and anodic and cathodic Tafel slopes ( β a and β c ) were obtained via the Tafel extrapolation method. 33 The inhibition efficiency ( η PDP ) was derived from the following formula: 34,35 where i corr,0 and i corr represent the corrosion current densities without and with the NBLT additive, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…32 The relevant electrochemical parameters including corrosion potential ( E corr ), corrosion current density ( i corr ), and anodic and cathodic Tafel slopes ( β a and β c ) were obtained via the Tafel extrapolation method. 33 The inhibition efficiency ( η PDP ) was derived from the following formula: 34,35 where i corr,0 and i corr represent the corrosion current densities without and with the NBLT additive, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, from the gravimetric test with 4 g/L Arachis hypogaea shell extract, 98.42% efficiency was derived. This efficiency is greater than most of the reported green inhibitors [24][25][26][27]. The process of extracting most inhibitors with efficiency lower than Arachis hypogaea shell extracts are expensive.…”
Section: Comparative Efficiency and Economic Studiesmentioning
confidence: 86%
“…Popoola et al investigated the influence of avocado seed extracts on the corrosion of API X 65 pipeline steel in 1 M H 2 SO 4 solutions and found 88% efficiency with 5 g L −1 inhibitor [24]. Amal A Altalhi showed that diazenebased Schiff base derivatives showed 90.4 and 92.6% efficiency on API stainless steel at 100 ppm concentration [25]. In another effort, Alao et al used 5 g Persea Americana seed extract in 1 M HCl media and achieved 95.65% efficiency [26].…”
Section: Introductionmentioning
confidence: 99%
“…Diluted acidic solutions are commonly used for various applications, including metal surface preparation, sanitizing industrial machinery, removing mineral deposits through acidification, and acidizing oil wells, all of which can cause significant corrosion in iron and steel . These tasks come with the disadvantage that the intense acidic exposure dissolves the metal, resulting in defects or potentially inducing permanent structural weakness in essential machine elements . As a result of the substantial financial losses and security risks stemming from corrosion in numerous industrial domains, safeguarding metal structures has garnered significant focus.…”
Section: Introductionmentioning
confidence: 99%